Duets recorded in the wild reveal that interindividually coordinated motor control enables cooperative behavior - Susanne Hoffmann (Nature Portfolio, 2019)
Recording neural activity during coordinated behaviors in controlled environments limits opportunities for understanding natural interactions. Here, the authors record from freely moving duetting birds in their natural habitats to reveal the neural mechanisms of interindividual motor coordination.